2014
DOI: 10.1080/17480272.2014.949855
|View full text |Cite
|
Sign up to set email alerts
|

Optical performance of finished and unfinished tropical timbers exposed to ultraviolet light in the field in Costa Rica

Abstract: This study evaluated wood color change (ΔE*) and the surface quality in 10 tropical wood species painted with three finishes (composed of wax and polyurethane). Two weathering conditions were tested: natural weathering (NW) and artificial weathering (AW). The results showed that the application of these finishes, decreased the luminosity (L*), increased the redness (a*) and the yellowness (b*) parameters in all species. ΔE*, after weathering exposure, was affected significantly by L*, a*, and b, whereas for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…A possible explanation for this observation is that the specific type and content of different extractives in massaranduba wood influenced the colour change of the pigment in the used oil. Effect of different species of tropical woods on their colour stability after treatment with pigmented paints was also found in other works [19,24,25].…”
Section: Effect Of Tropical Wood Species On Weatheringsupporting
confidence: 74%
See 2 more Smart Citations
“…A possible explanation for this observation is that the specific type and content of different extractives in massaranduba wood influenced the colour change of the pigment in the used oil. Effect of different species of tropical woods on their colour stability after treatment with pigmented paints was also found in other works [19,24,25].…”
Section: Effect Of Tropical Wood Species On Weatheringsupporting
confidence: 74%
“…For example, the negative effect of the initial lighter colours of wood was described by Salas et al [19], the negative effect of a smaller density of wood in the works of Kataoka et al [23] and Williams et al [8], and the effect of rougher wood surface in the works of Van den Bulcke et al [24] and De Windt et al [25]. The naturally darkest wood species-massaranduba (see L* value was 49.0 in Table 1) darkened in an exterior at least (see DL* in Fig.…”
Section: Effect Of Tropical Wood Species On Weatheringmentioning
confidence: 86%
See 1 more Smart Citation
“…Wood samples were exposed in the province of Cartago in Costa Rica (9°50¢59 †N; 83°54¢37 †W). The climatic conditions were widely detailed by Valverde and Moya 23 and Salas et al 25 For accelerated weathering (AW), UV exposure was administered by means of a weathering Q-Lab chamber (QUV/spray model). The ASTM G154-12a standard was used for this test.…”
Section: Wood Color Evaluationmentioning
confidence: 99%
“…However, although limited, there are some studies on the behavior of various varnishes in tropical lumber, such as those on Cedrela odorata, Carapa guianensis, Tectona grandis, and Acacia mangium. [23][24][25] Degradation of the surface of the varnish (in color and appearance) on wood in the open air is one of the disadvantages of the varnishes. 26 Different studies 18,21,22 have found that ultraviolet (UV), visible, and infrared light are the ones generating the greater chemical reactions in the components of the wood and the varnish, causing degradation of the latter.…”
Section: Introductionmentioning
confidence: 99%